2021
DOI: 10.1186/s12893-021-01251-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ruiyun procedure for hemorrhoids combined simplified Milligan–Morgan hemorrhoidectomy with dentate line-sparing in treating grade III/IV hemorrhoids: a retrospective study

Abstract: Background Hemorrhoids are common. Hemorrhoidectomy should typically be offered to patients whose symptoms result from external hemorrhoids or combined internal and external hemorrhoids with prolapse (grades III/IV). However, none of the currently used surgical methods could be considered an ideal surgical option that is effective, safe, and painless. We hypothesized that a combination of Ruiyun procedure for hemorrhoids (RPH) and simplified Milligan–Morgan hemorrhoidectomy (sMMH) will increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…To our knowledge, the recovery of anal function is a key measure of the clinical efficacy of patients with mixed hemorrhoids. A good anal function can significantly improve the quality of life of patients and relieve complications such as bloody stool and defecation difficulties in patients [ 20 ]. The results showed that the anal function of the patients in the combined group was superior to the operation group, with a good safety profile.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the recovery of anal function is a key measure of the clinical efficacy of patients with mixed hemorrhoids. A good anal function can significantly improve the quality of life of patients and relieve complications such as bloody stool and defecation difficulties in patients [ 20 ]. The results showed that the anal function of the patients in the combined group was superior to the operation group, with a good safety profile.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients should not eat fast spicy, salty, greasy food, and other stimulating food to avoid dry stool. Patients should eat more vegetables, fruits, lean meat, eggs and other nutritious food after surgery [14][15][16][17] .…”
Section: The Eating Nursing On the Curing Ring Mixed Hemorrhoidsmentioning
confidence: 99%
“…However, its incidence in young people is also not unusual. 4 While the prevalence in the world remains undetermined, a clinical study has discovered an overall 39% incidence for Grades 1–4 hemorrhoids, which was categorized according to the international classification of hemorrhoids in the adult population. 5 Treatment modalities for hemorrhoids vary depending on the severity and may include lifestyle modifications, topical medications, and surgical techniques for more complicated cases.…”
Section: Introductionmentioning
confidence: 99%